2022
DOI: 10.1177/09603271221080235
|View full text |Cite
|
Sign up to set email alerts
|

AgNPs reduce reproductive capability of female mouse for their toxic effects on mouse early embryo development

Abstract: Silver nanoparticles (AgNPs) are widely applied in the field of personal protection for their powerful toxic effects on cells, and recently, a new type of vaginal gel with AgNPs is used to protect the female reproductive tract from microbes and viruses. However, a high risk of AgNPs to the fetus and the underlying mechanism of AgNPs to interfere in embryo development still remain unclear. Thus, this study investigated the impact of two drugs of vaginal gel with AgNPs on reproductive capability of the female mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Collection of GV-stage, MII-stage oocytes, and pronuclear-stage embryos: As described in literatures [41,42], in brief, 6-8 week-old female ICR mice were injected intraperitoneally with 10 IU of Pregnant Mare Serum Gonadotropin. (PMSG, Ningbo Sansheng Pharmaceutical Co., Ltd.).…”
Section: Oocyte Collection In Vitro Maturation In Vitro Fertilization...mentioning
confidence: 99%
See 1 more Smart Citation
“…Collection of GV-stage, MII-stage oocytes, and pronuclear-stage embryos: As described in literatures [41,42], in brief, 6-8 week-old female ICR mice were injected intraperitoneally with 10 IU of Pregnant Mare Serum Gonadotropin. (PMSG, Ningbo Sansheng Pharmaceutical Co., Ltd.).…”
Section: Oocyte Collection In Vitro Maturation In Vitro Fertilization...mentioning
confidence: 99%
“…In vitro fertilization (IVF): Matured oocytes were incubated in HTF medium (MR-070-D, Milipore) containing 10µL of capacitated sperm suspension obtained as described above at 37°C with 5% CO 2 for 4-6 hours [42,44]. The fertilization rate was calculated based on the formation of pronuclear and the extrusion of the second polar body.…”
Section: Oocyte Collection In Vitro Maturation In Vitro Fertilization...mentioning
confidence: 99%
“…Furthermore, Kunming mice administrated with AgNPs at 11.61 nm via tail vein injection showed a significant increase in the rate of embryo resorption [ 51 ]. Notably, a recent study found that commercial drugs of vaginal gels containing AgNPs impaired mammalian embryo development, despite no apparent impairments in the reproduction of ICR female mice, a mouse strain from the Institute of Cancer Research and therefore called ICR mice in short [ 53 ]. Additionally, AgNPs hindered the development of in vitro fertilization embryos in particle size- and dose-dependent manner [ 53 ].…”
Section: Hazardous Impacts Of Agnps On Embryosmentioning
confidence: 99%
“…Notably, a recent study found that commercial drugs of vaginal gels containing AgNPs impaired mammalian embryo development, despite no apparent impairments in the reproduction of ICR female mice, a mouse strain from the Institute of Cancer Research and therefore called ICR mice in short [ 53 ]. Additionally, AgNPs hindered the development of in vitro fertilization embryos in particle size- and dose-dependent manner [ 53 ]. Overall, exposure to AgNPs during pregnancy through various routes, such as pulmonary exposure or intravenous injection, can lead to embryotoxicity across different strains.…”
Section: Hazardous Impacts Of Agnps On Embryosmentioning
confidence: 99%